Unveiling four decades of spatiotemporal climate trends in Texas (1981–2023) - M.Shahriar Sonet; Yunuen Reygadas (Journal of Hydrology: Regional Studies, 2025)
Study Region: Texas, U.S.A. Study Focus: Understanding climate variability is critical in Texas, a region influenced by moist air from the Gulf of Mexico and arid air from the Mexican Plateau. We investigated trends in annual and monthly mean temperature, total precipitation, and mean specific humidity, along with their monthly variability, from 1981 to 2023. We applied the modified Mann-Kendall test and Theil-Sen slope estimator to PRISM and GridMET 4-km datasets. New Hydrological Insights for the Region: The most pronounced changes occurred during early summer, with Central Texas experiencing precipitation declines up to 125.27 mm and Far West Texas exhibiting temperature increases up to 3.68°C and humidity decreases up to 2.33 g/kg. A northwest–southeast gradient in humidity trends was observed, with declines across the Panhandle and increases near the Coast. Variability trends were more spatially and temporally extensive. Temperature variability increased from spring through fall by up to 1.19°C, particularly in Far West Texas. Precipitation variability intensified in May, August, and September, with swings up to 320 mm, especially in Central, Eastern, and Southern Texas. Humidity variability peaked in July and August in North Central and East Texas (up to 0.63 g/kg), while South Texas showed consistent declines. This reveals a growing climatic divide between humid and arid regions and underscores the need for adjusting cropcalendars, upgrading stormwater-systems, and expanding irrigation-infrastructure.